Public Policy Formulation and Public Disobedience: Conceptual Lessons from Tanah Awu People Movement - Dwiyanto Indiahono (Universitas Riau, 2009)
Local government in long time has wished to build international airport in Tanah Awu –Lombok Tengah – Nusa Tenggara Barat Province. Pro and contra to this plan happened sincebuilding plan published by government. In a period of new order, some of local residents have gotcompensation and some of other not yet got it. Problems emerge when building plan will be started:Public disobedience for building plan in the reality was done by resident who have got compensa-tion and haven’t got compensation. Public disobedience by farmer of Tanah Awu for internationalairport in their land has left many important lessons for the public policy formulation. This article willgive conceptual answer for problems of public disobedience and public policy making in this case.The conceptual answers for public policy formulations are: First, public in the future have tomanage aspiration better and submit the aspiration to government more democratically. Second,government have to: create dialogue rooms for public who giving criticism and input to everypolicy; have commitment and try create pro poor policy maximally; create policy framework thatcapable to give win-win solution for all stakeholders.